Transient Dynamics of Stimulated Raman Scattering in Gas-Filled Hollow-Core Photonic Crystal Fibers - Yashar E. Monfared (Advances in Materials Science and Engineering)
A theoretical and numerical investigation of transient dynamics of stimulated Raman scattering (SRS) inside gas-filled hollow-core photonic crystal fibers (HCPCFs) is reported here. A clear link between the transient dynamics and the coherent memory of the SRS interaction is demonstrated. In addition, the role of pulse width, pump power, fiber length, and gaseous medium in the transient dynamics of SRS in HCPCFs is discussed. It is shown that the coherent memory can serve as a convenient parameter to control the SRS propagation regime.